PERANAN TENAGA KERJA DAN INVESTASI TERHADAP PRODUKSI INDUSTRI PENYULINGAN NILAM DI KABUPATEN ACEH JAYA - Reza Septian Pradana (Universitas Medan Area, 2020)
Aceh Jaya regency becomes the best patchouli producing area in Aceh. Patchouli oil levels produced above 30 percent make patchouli produced in Aceh Jaya have high economic value. This condition should be able to increase the passion of patchouli distillation industry in Aceh Jaya Regency. However, the development of the patchouli distillation industry cannot be separated from the role of labor and investment in the industry. This study aims to analyze the role of labor and investment to production of patchouli distillation industry in Aceh Jaya Regency. The sample in this study was 51 micro and small scale patchouli distillation industries in Aceh Jaya Regency. This study uses multiple regression analysis. The result of estimation shows that investment significantly gives positive influence to production patchouli distillation in Aceh Jaya Regency while labor insignificantly influents to production of patchouli distillation industry in Aceh Jaya Regency. Thus, local government and relevant agencies have to be able to increase the interest of investor and gives training both managerial and technical to increase the workers’ quality of patchouli distillation industry in Aceh Jaya Regency.